ANALISIS PENGARUH FAKTOR-FAKTOR EKSTERNAL DAN INTERNAL TERHADAP KEPATUHAN WAJIB PAJAK ( Studi pada Wajib Pajak yang terdaftar di Kantor Pelayanan Pajak PRATAMA Kota Yogyakarta ) - Sukron Makmun (AKT 15 UMY 432, 2015)
*432 This study aims to determine the positive influence of the variables attitude, behavioral control, the intention of the taxpayer, knowledge, understanding, quality of service and tax penalties on tax compliance and the negative effects of subjective norms on tax compliance. This research was conducted at taxpayer registered in the Tax Office PRATAMA Yogyakarta using 73 respondents in the sample to be studied. Sampling using purposive sampling method. Data collection techniques using a questionnaire that was distributed directly to the taxpayer and data analysis using descriptive statistics test, the test consists of the classical assumption of normality test, test, multicollinearity test, test and test hypotheses heteroskeidastisitas using multiple regression test. Results showed: 1) The attitude of no significant impact on taxpayer compliance, 2) Control keprilakuan no significant effect on tax compliance, 3) Intention positive effect on tax compliance, 4) Norma subjectively positive effect on tax compliance, 5) Knowledge and understanding no significant effect on tax compliance, 6) Quality of care has positive effect on tax compliance. 7) Sanctions taxation no significant effect on tax compliance